An improved method for improving the calculation accuracy of marine low-resistance shale reservoir parameters - Li, Menglei; Zhang, Chaomo (Frontiers in Earth Science, 2022)
In order to accurately evaluate the shale reservoir of the Lower Carboniferous Luzhai Formation in the central Guangxi area, in view of the influence of the low resistivity of the reservoir and the complex mineral composition on the logging response, taking Well A1 as an example, a method to improve the calculation accuracy of reservoir parameters is studied. The reasons for the low resistance in the study area are analyzed from the aspects of minerals, geochemistry and geology. An improved △log R method based on borehole correction and natural gamma spectroscopy logging was proposed to calculate the total organic carbon content. A calcium-corrected HERRON method is proposed to calculate porosity. The P/S time difference ratio-density neutron log overlap difference is proposed to calculate saturation. Calculation of adsorbed gas content based on organic matter correction. The results show that the improved method greatly improves the prediction accuracy, and has high consistency with the core analysis results, and can accurately evaluate the shale reservoirs of the Lower Carboniferous Luzhai Formation in the central area of Guangxi. The improved new method has good applicability and can be further used in the evaluation of this kind of source rock reservoir.